The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2016
DOI: 10.2147/cwcmr.s93615
|View full text |Cite
|
Sign up to set email alerts
|

Peristomal skin complications: causes, effects, and treatments

Abstract: Enterostomal formation remains a necessary part of multiple types of surgeries. Stomal difficulties can be a source of frustration for patients; however, a properly functioning stoma in a patient educated in its care can result in a highly functional individual, with a high quality of life, comparable to a person without a stoma. Correct surgical technique is vital to creating a stoma that is sufficiently everted, and in a good anatomical location. Loop ileostomies have a higher chance of complications, thus c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 14 publications
1
26
0
2
Order By: Relevance
“…Complications ranges from mild irritation to full thickness ulcerations leading to pain anxiety, and in some cases signifi cant social isolation related to the pouching system leaks. 4,5 Our fi nding is consistent with this study as 38% of ileostomy people have Peristomal skin excoriation. Inappropriate stoma site, not fi tting ostomy appliances, wrong selection of appliances, inappropriate technique of changing appliances are some of the causes of leaking.…”
Section: Discussionsupporting
confidence: 90%
“…Complications ranges from mild irritation to full thickness ulcerations leading to pain anxiety, and in some cases signifi cant social isolation related to the pouching system leaks. 4,5 Our fi nding is consistent with this study as 38% of ileostomy people have Peristomal skin excoriation. Inappropriate stoma site, not fi tting ostomy appliances, wrong selection of appliances, inappropriate technique of changing appliances are some of the causes of leaking.…”
Section: Discussionsupporting
confidence: 90%
“… 1 , 2 Stomal and peristomal complications are attributable to various causes including moisture-associated skin damage with exposure to stomal effluent, mechanical trauma to the peristomal skin or hair follicles (eg, stripping injury and pressure injuries) due to the ostomy system or ostomy accessories, immunologic responses (hypersensitivity or allergic), and infections. 2 5 One study estimated that peristomal skin complications (PSCs) account for 40% of all visits to ostomy care nurses. 6 Over an approximate 7-week treatment period, a panel of 11 experienced stoma care nurses estimated the costs of treatment of PSCs to range from €23.10 (US $26.80) for mild cases to €141.20 (US $163.79) for severe cases (all assume typical care rendered in France and are in 2011 Euros).…”
Section: Introductionmentioning
confidence: 99%
“…Some of the studies found more skin problems among individuals with loop stomas and others found more skin problems among individuals with end stomas. Doctor and Colibaseanu [25] reported that individuals with loop stomas have higher incidence of PSCs. More specifically, loop ileostomy is the main cause of the development of peristomal skin excoriation because of the higher enzyme and watery content present in the proximal loop of ileum.…”
Section: Discussionmentioning
confidence: 99%
“…Carlsson et al [53] stated that prevalence of PSCs is mainly related to the construction of ostomies. Doctor and Colibaseanu [25] reported that in general, insufficient protrusion and a structure of loop stoma that is too flat lead to pooling of ostomy effluent in the stoma site and the development of PSCs. Kann [40] and Vujnovich [54] found that poorly shaped stomas and low stomal height are factors that contribute to developing peristomal skin excoriation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation